The effects of video modeling on staff implementation of behavioral procedures in China. (25th August 2020) - Lim, Nataly; Hu, Xiaoyi
Abstract: The purpose of the present study was to evaluate the effectiveness of a video modeling (VM) procedure at teaching three staff members who were working with children with autism spectrum disorder (ASD) to implement a token economy, use an error correction procedure, and conduct a multiple stimulus without replacement preference assessment. The study was conducted at a summer camp for children with ASD located on a university campus and at a school for students with special needs in mainland China. All participants successfully generalized instructional skills learned during the VM intervention to sessions with children with ASD. Maintenance of instructional skills was also seen during follow‐up. These results indicate VM to be an economical and effective approach to training staff to implement various behavioral strategies. Moreover, the validity of VM as an effective intervention for staff training is increased by inclusion of blind ratings by five Board Certified Behavior Analysts.